1998
DOI: 10.1093/arclin/13.7.575
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contributions of Cognitive and Motor Component Processes to Physical and Instrumental Activities of Daily Living in Parkinson's Disease

Abstract: Patients with Parkinson's disease (PD) become dependent upon caregivers because motor and cognitive disabilities interfere with their ability to carry out activities of daily living (ADLs). However, PD patients display diverse motor and cognitive symptoms, and it is not yet known which are most responsible for ADL dysfunction. The purpose of this study was to identify the contributions that specific cognitive and motor functions make to ADLs. Executive functioning, in particular sequencing, was a significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 0 publications
7
79
1
1
Order By: Relevance
“…Scores from the full set of neuropsychological assessments assessing EF were combined into a composite score representing the conceptually motivated construct of EF [21] using a method advocated by Cohen et al [73] and Cahn et al [74]. Each of the five measures was converted into a Z score and valenced such that lower scores indicated poorer performance.…”
Section: Resultsmentioning
confidence: 99%
“…Scores from the full set of neuropsychological assessments assessing EF were combined into a composite score representing the conceptually motivated construct of EF [21] using a method advocated by Cohen et al [73] and Cahn et al [74]. Each of the five measures was converted into a Z score and valenced such that lower scores indicated poorer performance.…”
Section: Resultsmentioning
confidence: 99%
“…We performed screening tests and scales that have been widely used in a routine clinical practice. In line with studies [6,[8][9][10] we hypothesized that in contrast to basic ADL outcomes, the IADL impairment as measured by the Lawton's IADL questionnaire [11,12] would better reflect cognitive than motor deficits in PDD, thus making the questionnaire a valuable tool in the process of diagnosing PDD in addition to AD.…”
Section: Introductionmentioning
confidence: 82%
“…Results of a study performed on PD patients who were candidates for pallidotomy [9] again showed that motor functioning was a significant predictor of basic ADL ability, while it was not a predictor for IADL ability. On the other hand, cognitive outcomes were correlated with IADL in PD patients with and without dementia [10].…”
Section: Introductionmentioning
confidence: 99%
“…Key secondary outcomes of clinical importance have been identified and include: (1) Time to initiation of ST has been used as a primary outcome measure in several previous studies of putative disease‐modifying agents5, 29 and reflects progression early in disease not obscured by symptomatic therapy; (2) Time to and severity of motor complications may reflect a secondary measure of progression once type of initial symptomatic treatment is accounted for30, 31; (3) A potential beneficial effect of isradipine on disease progression could be masked by differential usage of ST. To account for this factor, we will evaluate differential use of ST by calculating the levodopa equivalent dosages between treatment groups32; (4) Incidence and severity of nonmotor symptoms, as these contribute disproportionately to quality of life and reflect clinically relevant outcomes in PD 33, 34, 35…”
Section: Methodsmentioning
confidence: 99%